Ana Maria Poppovic e a Educação de Crianças Menores de 10 anos: uma análise de suas ideias educacionais - Chiari, Camila Maria (2019)
The research has as a proposal to capture, understand and analyze the educational ideas of the Pedagogue and psychologist Ana Maria Poppovic, reference researcher mainly between the decades of 1970 and 1980. Prominent intellectual in the educational setting for conducting several studies, projects, researches and work in defense of early childhood education and literacy. Poppovic had collaborationmany times with partnerships of scholars and researchers in the field of education and psychology. At the same time he obtained support and collaboration of a group of scholars, to defend his ideas, took on a leadership role and responsibility in the face of investigations. So, we understand that this research is related to studies of trajectory of Poppovic, but belongs to the field of History of Education and the construction of their ideas, as is dedicated to understanding the work and intellectual studies within your period and historical context by examining their contributions to the brazilian education. We are interested that Ana Maria Poppovic became interested in preschool in order to contribute to the promotion of children "able" and "ready" for literacy. Poppovic was in the field of early childhood education a space to meet and even eradicate the problems and difficulties of literacy in the early grades of elementary school. So, has developed numerous studies and research, and as a result, publications, activities, projects and practical educational materials, mainly for children spoken as "cultural marginalisation", children with difficulties in the learning and belonging to an economically disadvantaged group. We opted for the investigative research in method of theoretical character with the intention of bibliographic understanding educational practices through the context and of the factors that limit. We use mainly the conceptions of Depaepe (2006; 2012) to analyze the ideas of this intellectual from the concept of "demythologization", in an attempt to understand the real reasons and the contradictions that have allowed and took Poppovic to present his proposals for education. We conclude that Poppovic had influence of productions and international programs, especially Head Start, a study developed in the United States with a proposal to follow the teaching-learning and development of poor children. Along your trajectory Poppovic also collaborated and proposed studies international proposals that were adapted to the national context. His educational ideas were related mainly to marginalized children culturally and so supported in defense of early childhood education with dedication to literacy and readiness with Compensatory education to provide defense poor children conditions favourable for the teaching-learning process. So, we believe this research collaborates with the Brazilian educational space reconstruction from an educator of great importance to Education and the History of Education.